Susceptibility of cockroaches (Gromphadorhina portentosa, Nauphoeta cinerea and Blaptica dubia) exposed to entomopathogenic nematodes. Issue 4 (3rd April 2017) - Cutler, James; Hughes, Kathryn; Rae, Robbie
ABSTRACT: Cockroaches are major pests, vectors of pathogenic bacteria and induce allergies. Current control methods use chemical pesticides, but they can be ineffective and costly and there are reports of resistance in the field; hence new control methods are needed. There are conflicting reports about the susceptibility of cockroaches to entomopathogenic nematodes (EPNs); so we investigated if EPNs could kill several diverse cockroach species, including the Madagascan hissing roach ( Gromphadorhina portentosa ), the Lobster roach ( Nauphoeta cinerea ) and Blaptica dubia . Female adult cockroaches were exposed to either commercial products containing Steinernema kraussei or a combination of Heterorhabditis spp. and Steinernema spp. at 50 and 150 nematodes per cm 2 for 21 days. We also monitored feeding and the numbers of infective juveniles that were produced from each cockroach corpse. We found that S. kraussei were harmless to all cockroach species (at both doses) but when exposed to a mixture of Heterorhabditis spp. and Steinernema spp. B. dubia died after 6 days and its feeding was strongly inhibited. We also found that the mixture of Heterorhabditis spp. and Steinernema spp. could proliferate in the cadavers of B. dubia whilst S. kraussei could only reproduce in G. portentosa and B. dubia but not N. cinerea . In conclusion, S. kraussei was harmless to all three cockroach species but B. dubia was killed when exposed to Heterorhabditis spp. and Steinernema spp., highlighting the differences in the host range of EPNs.